Hypo-q-norms on a cartesian product of algebras of operators on Banach spaces - Dragomir, Silvestru Sever (Annales Mathematicae Silesianae, 2020)
In this paper we consider the hypo-q-operator norm and hypo-q-numerical radius on a Cartesian product of algebras of bounded linear operators on Banach spaces. A representation of these norms in terms of semi-inner products, the equivalence with the q-norms on a Cartesian product and some reverse inequalities obtained via the scalar reverses of Cauchy-Buniakowski- Schwarz inequality are also given.